Exploring Factors That Lead to Students Dropout in Public Secondary Schools in Al’Ain - Alkaabi, Fatima Khamis Abdulla; Mohd Asri Bin Mohd Noor (European Journal of Multidisciplinary Studies, 2020)
For any educational institution, students are most important. Universities and colleges have no value without students. The educational process is an integrated process involving the family, the school and the entire community to reach effective outputs. There are a number of factors that negatively affect at-risk students’ retention in school and graduate such as socioeconomic status. Phenomenon of dropout where thousands of students dropped out is prevalent and constant in urban schools across the United States (Brown, 2015). This research is important for academic reason; it gives academic practitioners vital information that can be utilized to develop the education. The information was collected by interviews questions with students. The information collected were analyzed by using coding and theme with Nvivo program. The research showed that the factors affect in Retention of secondary stage’s students in Al Ain.